An Efficient GPU-based Time Domain Solver for the Acoustic Wave Equation - Mehra, Ravish; Raghuvanshi, Nikunj; Savioja, Lauri; Lin, Ming C.; Manocha, Dinesh (Applied Acoustics, 2011)
An efficient algorithm for time-domain solution of the acoustic wave equation for the purpose of room acoustics is presented. It is based on adaptive rectangular decomposition of the scene and uses analytical solutions within the partitions that rely on spatially invariant speed of sound. This technique is suitable for auralizations and sound field visualizations, even on coarse meshes approaching the Nyquist limit. It is demonstrated that by carefully mapping all components of the algorithm to match the parallel processing capabilities of graphics processors (GPUs), significant improvement in performance is gained compared to the corresponding CPU-based solver, while maintaining the numerical accuracy. Substantial performance gain over a high-order finite-difference time-domain method is observed. Using this technique, a 1 s long simulation can be performed on scenes of air volume 7500 m3 till 1650 Hz within 18 min compared to the corresponding CPU-based solver that takes around 5 h and a high-order finitedifference time-domain solver that could take up to three weeks on a desktop computer. To the best of the authors’ knowledge, this is the fastest time-domain solver for modeling the room acoustics of large, complex-shaped 3D scenes that generates accurate results for both auralization and visualization.